2011
DOI: 10.1021/ac201096f
|View full text |Cite
|
Sign up to set email alerts
|

Diffraction-Based Tracking of Surface Plasmon Resonance Enhanced Transmission Through a Gold-Coated Grating

Abstract: Surface plasmon resonance enhanced transmission through metal-coated nanostructures represents a highly sensitive yet simple method for quantitative measurement of surface processes and is particularly useful in the development of thin film and adsorption sensors. Diffraction-induced surface plasmon excitation can produce enhanced transmission at select regions of the visible spectrum, and wavelength shifts associated with these transmission peaks can be used to track adsorption processes and film formation. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…The development of metal-dielectric nanocomposite materials with plasmonic properties is of great interest for many applications such as sensing 1 , SERS 2 , photonics 3 and photovoltaics 4,5 . In particular, it has been shown that plasmonic nanoparticle gratings (PNG) can offer new detection schemes in bio-sensing and can significantly improve the detection sensitivity [6][7][8] . For this purpose, polymers, as host matrices, offer several advantages in terms of processing, optical transparency and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…The development of metal-dielectric nanocomposite materials with plasmonic properties is of great interest for many applications such as sensing 1 , SERS 2 , photonics 3 and photovoltaics 4,5 . In particular, it has been shown that plasmonic nanoparticle gratings (PNG) can offer new detection schemes in bio-sensing and can significantly improve the detection sensitivity [6][7][8] . For this purpose, polymers, as host matrices, offer several advantages in terms of processing, optical transparency and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…This RI sensitivity allows for high throughput label free sensing/diagnostics [26][27][28][29][30][31] and thin film deposition tracking. [32][33][34][35][36][37][38][39][40] Additionally, because SPR peak shift can be tracked versus time, kinetics and binding affinity can be elucidated. 19,41,42 The first commercial SPR instrument for binding affinity was sold in 1990 under the name of BIACORE.…”
Section: Surface Plasmon Resonance Interests and Application Fieldsmentioning
confidence: 99%
“…Surface plasmon resonance (SPR) is a powerful and highly versatile optical phenomena utilized for various analytical measurements such as label free sensing of adsorption, 99 measurement of binding affinities, 19,41,42 and monitoring thin film deposition. 32,35,38,39 These measurements exploit SPR's sensitivity to changes in surface optical properties, 25,90 namely deviations in near-field optical parameters such as refractive index. The enhanced surface electric field associated with SPR can also be used to enhance or amplify surface spectroscopies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations